Rock of ages [videorecording (Blu-Ray)] - Anders, Adam; Astrom, Peer (Distributed by Warner Home Video, 2012)
Set in 1987 Los Angeles, a young woman and young man meet while pursuing their dreams of rock 'n' roll stardom.